Weighing human dignity and cloning from ethical and Islamic perspectives - Shuriye, Abdi Omar (Universiti Sains Islam Malaysia (USIM), 2006)
As a result of the expansion of scientific andtechnological innovations, bioethics as a field of study in the hierarchy of disciplines has emerged; it raises questions on human life, death, dignity, creativity, role of God in human innovation and moral values. This paper is on the ethics of cloning; the word cloning literally connotes a cell or group of cells, the process of human cloning may use a technique called Human somatic cell Nuclear Transfer. Clone also refers to organism descended asexually from a single ancestor. Then paper raises divers ethical questions related to cloning. The first ethical question on cloning involves in the origin of the clone and its relation to other humans as the clone child has no genetic father or mother in a family lineage. Another question is will the process affect the social identity, relationship and responsibility as these are widely connected to biological kinship? The paper also discuses the opinions of the advocates and opponents of cloning, it further weighs human dignity and cloning from a Qur'anic perspective.